Α-Glucosidase inhibition by flavonoids: an in vitro and in silico structure–activity relationship study. (1st January 2017) - Proença, Carina; Freitas, Marisa; Ribeiro, Daniela; Oliveira, Eduardo F. T.; Sousa, Joana L. C.; Tomé, Sara M.; Ramos, Maria J.; Silva, Artur M. S.; Fernandes, Pedro A.; Fernandes, Eduarda
Abstract: α-Glucosidase inhibitors are described as the most effective in reducing post-prandial hyperglycaemia (PPHG) from all available anti-diabetic drugs used in the management of type 2 diabetes mellitus . As flavonoids are promising modulators of this enzyme's activity, a panel of 44 flavonoids, organised in five groups, was screened for their inhibitory activity of α-glucosidase, based on in vitro structure–activity relationship studies. Inhibitory kinetic analysis and molecular docking calculations were also applied for selected compounds. A flavonoid with two catechol groups in A- and B-rings, together with a 3-OH group at C-ring, was the most active, presenting an IC50 much lower than the one found for the most widely prescribed α-glucosidase inhibitor, acarbose . The present work suggests that several of the studied flavonoids have the potential to be used as alternatives for the regulation of PPHG. Graphical Abstract: